2022
DOI: 10.1088/1757-899x/1225/1/012004
|View full text |Cite
|
Sign up to set email alerts
|

A review on transition metal oxides based nanocomposites, their synthesis techniques, different morphologies and potential applications

Abstract: In the field of nanotechnology and nanoscience, transition metal oxides based nanocomposites (TMONCs) are promising for various application uses such as Supercapacitors, Sensors, Bactericidal properties, Photocatalytic Degradation, Solar Cells etc. Modification of transition metal oxide nanoparticles (TMONPs) to TMONCs by doping/mixing of another transition metal and metal oxide, carbon based nanoparticles, conducting polymers etc. to achieve enhanced surface area, increasing surface activities or number of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 161 publications
0
18
0
Order By: Relevance
“…Comparing Figure 5(b) and 5(e), it can be seen that ZFO‐Fe 2 O 3 displayed the first circle discharge/charge specific capacity of 1251.1/795.4 mAh g −1 and initial coulombic efficiency (ICE) of 63.5 %, while ZFO‐Fe 2 O 3 /g‐C 3 N 4 was 2280.3/1550.3 mAh g −1 with initial coulombic efficiency of 67.9 %. The discharge/charge capacity of the g‐C 3 N 4 ‐doped materials were significantly better for first cycle, but the initial coulombic efficiency was still awful, which matched the properties of transition metal oxides [27] . The low ICE can be improved by a number of processes such as pre‐lithiation techniques, material doping/coating and surface modification [67] .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Comparing Figure 5(b) and 5(e), it can be seen that ZFO‐Fe 2 O 3 displayed the first circle discharge/charge specific capacity of 1251.1/795.4 mAh g −1 and initial coulombic efficiency (ICE) of 63.5 %, while ZFO‐Fe 2 O 3 /g‐C 3 N 4 was 2280.3/1550.3 mAh g −1 with initial coulombic efficiency of 67.9 %. The discharge/charge capacity of the g‐C 3 N 4 ‐doped materials were significantly better for first cycle, but the initial coulombic efficiency was still awful, which matched the properties of transition metal oxides [27] . The low ICE can be improved by a number of processes such as pre‐lithiation techniques, material doping/coating and surface modification [67] .…”
Section: Resultsmentioning
confidence: 96%
“…Unfortunately, iron‐based metal oxides have large theoretical specific capacities, but large volume expansion (>200 %) and poor electrical conductivity during cycling limit the development of this type of materials [26] . It has been found that reducing the size of materials to the nanometer level, modifying the morphology of the materials or compositing with other materials such as carbon or polymeric conductive polymers, which can effectively reduce the disadvantages of volume expansion and easy pulverization, and increase the electrical conductivity [27,28] . Yue et al [29] .…”
Section: Introductionmentioning
confidence: 99%
“…The components, structure, and interfacial interactions of each specific property have a significant impact on them. In addition to improved economic potential for a number of industrial sectors that are highly beneficial to humanity and the environment [19,20]. Metal doped SnO2, conducting polymers/SnO2, transition metal oxides (TMOs)/SnO2, graphene/SnO2, and other important SnO2 based nanocomposites have been used in solar cells, SCs, Li-ion batteries, water purification, catalysis, sensors, medicine, electronics devices, and other sectors.…”
Section: Sno2 Nanoparticles (Sno2 Nps) and Sno2-based Nanocompositesmentioning
confidence: 99%
“…Hence, there is significant interest in developing rapid and cost-effective alternatives. Compact or portable devices, such as electrochemical bio/chemical sensors, present potential solutions as alternative approaches to traditional analytical methods. …”
Section: Introductionmentioning
confidence: 99%